Analisis Tingkat Kebisingan Pesawat Saat Take-Off Berdasarkan Variasi Tinggi Lintasan di Bandara Halim Perdanakusuma - Arindho Andrifa Faturrohman; Mufti Arifin; Ericko Chandra Utama (Jurnal Teknologi Kedirgantaraan, 2024)
An increase in flight frequency can have a negative impact on the surrounding environment, one of which is high noise levels. Noise can come from full activity, runway stay, movement towards the runway, or aircraft engine testing. Airplane noise during take-off is one of the environmental problems that need attention at airports. The height of the aircraft's trajectory during take-off can affect the noise level generated by the aircraft, but not much research has been conducted to measure the impact of variations in the height of the disturbance on the noise level of aircraft at Halim Perdanakusuma Airport. This study aims to measure the noise level of aircraft during take-off with variations in track height at Halim Perdanakusuma Airport. The method used in this study is to observe 4 aircraft taking off at Halim Perdanakusuma Airport with a research time of 3 days, and the measuring instrument used is a sound level meter. Sound level meters measure noise in dBA units between 30 and 130 dB at a frequency of 20 to 20.000 Hz. Based on the calculation and measurement results obtained, it is known that the maximum height when the measurement is on the second day is at point A of 277 meters, while at point B is 299 meters. While the highestnoise measurement at point A is 93,1 dB while at point B it is 91,5 dB. The measured noise value based on calculations is estimated at 66,2 dB and is still below the Airbus A320 aircraft noise certification for flyover takeoff of 73,7 dB.